Two new enigmatic species of Rhinebothrium (Cestoda: Rhinebothriidae) from the Persian Gulf: notes on generic traits and host specificity. Issue 3 (19th April 2021) - Golzarianpour, Kiavash; Malek, Masoumeh; Golestaninasab, Mehdi; Sarafrazi, Alimorad; Kochmann, Judith
Abstract : In the course of a three-year study conducted from January 2017 till November 2019, a total of 279 individuals belonging to 11 batoid species off northern coasts of the Persian Gulf and the Gulf of Oman were examined for the genus Rhinebothrium Linton, 1890 (Rhinebothriidea: Rhinebothriidae). Infection of Maculabatis randalli (Last, Manjaji-Matsumoto & Moore, 2012), M. arabica Manjaji-Matsumoto & Last et al., 2016, and Pateobatis fai (Jordan & Seale, 1906) with rhinebothriid cestodes is reported for the first time. In total, seven rhinebothriid species were recognized. Rhinebothrium klimpeli sp. nov. from Pateobatis fai and Rhi. atabaki sp. nov. from Maculabatis randalli are described herein. Both species differ from one another and their congeners on the basis of various characteristics of the scolex and proglottids. In order to create a DNA Barcoding library for local species and perform a phylogenetic analysis, different marker genes for seven species of Rhinebothrium were partially sequenced here for the first time; nuclear small subunit rDNA (SSU) and large subunit rDNA (LSU), and the Cytochrome c oxidase subunit I (COI) gene. Both Bayesian inference and maximum likelihood phylogenetic analyses using nuclear markers confirmed species boundaries recognized by morphological characteristics. Furthermore, both new species are classified into the genus Rhinebothrium based on molecular data. The description of Rhi. klimpeli sp. nov. leads us to modify the diagnosis of the genus Rhinebothrium in introducing the character 'bearing pre- and postvaginal testes' and 'lacking postovarian testes'. Rhinebothrium verticillatum (Subhapradha, 1955) is redescribed herein with designation of the neotype identified from the type host Rhynchobatus laevis (Bloch & Schneider, 1801) deposited at the Collection of the Zoological Museum, University of Tehran (ZUTC). All parasite species except Rhi. verticillatum were found in more than one host species from different families. Among them, Rhi. atabaki sp. nov. infects seven of 11 host species and seems to have the lowest host specificity. Furthermore, some implications for host specificity of rhinebothriid species are discussed. http://zoobank.org/urn:lsid:zoobank.org:pub:1CD0BC57-2741-4352-A7C5-CD6C36BF967C http://zoobank.org/urn:lsid:zoobank.org:act:9AA8D331-7936-49D7-8CA4-0B6BC927D0AC http://zoobank.org/urn:lsid:zoobank.org:act:5B21A19B-89E8-48E9-A0FF-FAB57387912F